A Preoperative Window-of-Opportunity Study of Oral SERD, Imlunestrant, in Newly Diagnosed ER-Positive, HER2-Negative Early Breast Cancer: Results from the EMBER-2 Study - Neven, Patrick; Stahl, Nicole; Vidal, Maria; Martín, Miguel; Kaufman, Peter A.; Harbeck, Nadia; Hunt, Kelly K.; Carter, Stacey; Bidard, Francois Clement; Fasching, Peter; Aftimos, Philippe; Wheatley, Duncan; et al. (Clinical Cancer Research, 2024)
Purpose: Imlunestrant is an oral selective estrogen receptor degrader with favorable safety and preliminary efficacy in patients with advanced breast cancer. Pharmacodynamic (PD) biomarker data can optimize drug dosing; in this study, we present PD data from the EMBER-2 study. Patients and Methods: Postmenopausal women with untreated, operable estrogen receptor (ER)-positive, HER2-negative early breast cancer were randomized to 400 versus 800 mg of imlunestrant daily for ∼2 weeks before surgery. A single arm study tested a daily dose of 200 mg. PD biomarker changes (ER, progesterone receptor, Ki-67 by IHC, and mRNA expression of ER-related genes) were evaluated in paired tumor samples (pre-/posttreatment). Safety and pharmacokinetics were also assessed. Results: Among evaluable paired samples (n 75), PD profiles demonstrated consistent ER targeting between 400- and 800-mg doses, with less toxicity at the 400-mg dose. Although inducing the lowest rate of complete cell-cycle arrest, PD and pharmacokinetic results were similar for the 200-mg dose. Conclusions: EMBER-2 combined with existing phase I data has identified 400 mg as the optimal imlunestrant dose.
CRIS-Team Scopus Importer:2025-02-04